Eigenvalue Rigidity in Nonnegative Ricci Curvature - Kulahci, Mihriban; Bektas, Mehmet (Int Electronic Journal Geometry, 2016)
Assume that M is a compact orientable Lorentz manifold with timelike boundary partial derivative M-t. If the Ricci curvature of M is bounded below by a positive constant k, then lambda(1) < (n - 1) max(M) |H| -k where lambda(1) is the first eigenvalue of the Laplacian of M.
Keywords: First Eigenvalue; Lorentz manifold; Nondegenerate timelike boundary